2020
DOI: 10.1186/s13045-020-00873-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant MRD negativity predicts favorable outcomes of CAR-T therapy followed by haploidentical HSCT for relapsed/refractory acute lymphoblastic leukemia: a multi-center retrospective study

Abstract: Background: Consolidative allogeneic hematopoietic stem cell transplantation is a controversial option for patients with relapsed/refractory acute lymphoblastic leukemia after chimeric antigen receptor T cell (CAR-T) therapy. We performed a multicenter retrospective study to assess whether patients can benefit from haploidentical hematopoietic stem cell transplantation after CAR-T therapy.Methods: A total of 122 patients after CAR-T therapy were enrolled, including 67 patients without subsequent transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 41 publications
9
44
0
Order By: Relevance
“…Park et al ( 9 ) reported that 17 of 53 patients received allo-HSCT after 19–28z CAR T-cell therapy, and their OS or LFS was not significantly different from those who did not undergo HSCT. In contrast, there is accumulating evidence supporting the benefit of consolidative HSCT ( 186 188 ). A multicenter retrospective study indicated that haploidentical HSCT after CD19 CAR T-cell therapy could benefit patients, with great improvement in LFS and OS compared with the nontransplant group (65.6% versus 32.8% P < 0.001; 77.0% versus 36.4%, P < 0.001) and no increased risk of treatment-related toxicity compared with previous values.…”
Section: Clinical Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al ( 9 ) reported that 17 of 53 patients received allo-HSCT after 19–28z CAR T-cell therapy, and their OS or LFS was not significantly different from those who did not undergo HSCT. In contrast, there is accumulating evidence supporting the benefit of consolidative HSCT ( 186 188 ). A multicenter retrospective study indicated that haploidentical HSCT after CD19 CAR T-cell therapy could benefit patients, with great improvement in LFS and OS compared with the nontransplant group (65.6% versus 32.8% P < 0.001; 77.0% versus 36.4%, P < 0.001) and no increased risk of treatment-related toxicity compared with previous values.…”
Section: Clinical Strategiesmentioning
confidence: 99%
“…A multicenter retrospective study indicated that haploidentical HSCT after CD19 CAR T-cell therapy could benefit patients, with great improvement in LFS and OS compared with the nontransplant group (65.6% versus 32.8% P < 0.001; 77.0% versus 36.4%, P < 0.001) and no increased risk of treatment-related toxicity compared with previous values. It also identified pretransplant MRD negativity as an important independent predictor of high LFS and OS ( 186 ). Gu et al ( 187 ) reported similar conclusions after analyzing 56 adults with R/R Ph+ ALL who received allo-HSCT post-CD19 CAR T-cell therapy.…”
Section: Clinical Strategiesmentioning
confidence: 99%
“…A long-term follow-up study indicated that late consolidative allo-HSCT (more than 80 days after CAR T-cell infusion) significantly increased the risk of death [33]. A recent published retrospective study indicated a lower incidence of relapse and a higher 2-year LFS in pre-transplant MRD-negative patients than in pre-transplant MRD-positive patients [53]. Besides, the relapse rate of MRD-negative CR patients was approximately 10% three months after CAR T-cell therapy [1,21,28].…”
Section: Therapeutic Window and Consolidative Allo-hsct Regimenmentioning
confidence: 99%
“…gov Identifier: NCT03533816, NCT03862833) about using γδ T cells for transplantation improvement are ongoing, but the results of these clinical studies have not been reported. Now HSCT following chimeric antigen receptor (CAR)-T therapy were reported favorable outcomes like higher OS and lower relapsed rate 98 , 99 . CAR-γδ T cells therapy was a novel promote immunotherapy for antitumor 100 and CAR-γδ T cells may be a potential immunological treatment to improve clinical outcomes of HSCT.…”
Section: γδ T Cells and Immunotherapymentioning
confidence: 99%